The influence of the complexing agent on the luminescence of multicolor-emitting Y2O3:Eu3+,Er3+,Yb3+ phosphors obtained by the Pechini's method - Oliveira, Nagyla A. [UNESP]; Bispo-Jr, Airton G. [UNESP]; Shinohara, Gabriel M.M. [UNESP]; Lima, Sergio A.M. [UNESP]; Pires, Ana M. [UNESP] (Elsevier, 2021)
In this study, it is reported the enhancement of the downshifting and the upconversion emission of Y2O3:Eu3+,Er3+,Yb3+ phosphor drove by sorbitol instead of the classic ethylene glycol used as polymerizing agent in the Pechini's synthesis. The RE3+ doping concentration was also varied to optimize the red or the green Er3+ emission or the Eu3+ red emission. Phosphors were obtained as high-crystalline and micro-sized particles, yet the doping concentration and the polymerizing agent influence the crystallite size and the lattice strain of the Y2O3 matrix that features optical band gap near to 5.6 eV. Under excitation at 378 nm, the downshifting emissions of Eu3+ and Er3+ are noticed, but under excitation at 463 nm, only the typical Eu3+ emission in the red spectral region is viewed. Contrarily, by exciting the phosphors at 980 nm within the IV spectral region, both green and red emissions of Er3+ plus the red emission of Eu3+ are seen through upconversion emission, and in this case, the pair Er3+/Yb3+ acts as sensitizers to the Eu3+ luminescence. Moreover, the use of sorbitol instead of ethylene glycol in the Pechini's synthesis enhances both downshifting and upconversion luminescence of phosphors due to a lowering of the Eu3+ local microssymmetry played by sorbitol, accordingly to the analyses of Judd-Ofelt intensity parameters of the phosphors. Finally, by varying the doping concentration, the polymerizing agent, and the excitation wavelength, the phosphor emission color may be tuned from the green towards the red spectral region.
Keywords: Luminescence; Photonic; Rare-earths; Spectroscopy; Upconversion